2011
DOI: 10.1007/s00586-011-1736-3
|View full text |Cite
|
Sign up to set email alerts
|

Autografts for spinal fusion: osteogenic potential of laminectomy bone chips and bone shavings collected via high speed drill

Abstract: In case of revision or minimal invasive spinal surgery, the amount of autograft possibly harvested from the lamina and the spinous processes is limited. Ekanayake and Shad (Acta Neurochir 152:651-653, 2010) suggest the application of bone shavings harvested via high speed burr additionally or instead, but so far no data regarding their osteogenic potential exist. Aim of the study was to compare the osteogenic potential of bone chips and high speed burr shavings, and to evaluate the applicability of bone shavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…10 Aerosol generating procedures, any medical procedure that can induce the production of aerosols of various sizes, 33 have come into focus as infection prevention and control advice is sought after by healthcare workers. Viable cells are contained in non-airborne surgical cutting by-products such as bone dust and chips, 18 , 41 , 54 but conflicting research exists regarding whether surgical smoke contains viable biological agents. For example viable melanoma cells were demonstrated in plume created by the electrocautery of mouse melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…10 Aerosol generating procedures, any medical procedure that can induce the production of aerosols of various sizes, 33 have come into focus as infection prevention and control advice is sought after by healthcare workers. Viable cells are contained in non-airborne surgical cutting by-products such as bone dust and chips, 18 , 41 , 54 but conflicting research exists regarding whether surgical smoke contains viable biological agents. For example viable melanoma cells were demonstrated in plume created by the electrocautery of mouse melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the quality of bone may play a more crucial role than volume. Eder et al 20 found laminectomy bone superior in terms of cell delivery, proliferation, and mineralization than bone collected after burring. By contrast, Patel et al 21 found in histological studies of burr shavings that viable cells without any obvious damage can be procured.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies have shown that for a single-level posterior lumbar fusion, local bone graft is equivalent to ICBG in fusion rate. 19 Furthermore, they found the average osteoblast mobilization was 1.25 Â 10 6 per gram from bone chips compared with 1.73 Â 10 5 cells per gram from bone shavings. 16 Some surgeons describe collecting bone shavings during decompression surgery to use as locally obtained autograft for the fusion portion of the surgery.…”
Section: Local Bone Graftmentioning
confidence: 99%
“…12 Although some surgeons believe local bone graft is inferior to ICBG, Sengupta et al 7 found similar fusion rates (80%) in singlelevel fusion using local autograft and ICBG. 18,19 However, the efficacy of these bone shavings has been called into question. [13][14][15] A systematic review of clinical studies comparing local bone graft and ICBG show similar fusion rates of 79% and 89%, respectively.…”
Section: Local Bone Graftmentioning
confidence: 99%